Mechanical Control of Rodents by using Wire- Box and Glue Traps in Sugar Cane Plantations at Sohag Governorate, Egypt (Global Journal of Science Frontier Research, 2021)
Abstract not found
Keywords: wire-box traps; glue traps; rodents; sugar cane; m Musculus